The Revitalization of Teacher Empowerment as Professionals in the Era 4.0 - Jamilus Jamilus (AT-TA'LIM, 2022)
This discussion aims to describe the revitalization of teacher empowerment as professional staff in the 4.0 era. This is important given the increasing challenges faced by education in the digital age. The era of globalization and information not only has a positive impact on the civilization of a nation, but can also have a negative effect on the attitude patterns and personality of the nation's children. Various forms of violence and deviations in values and norms that occur in the community, one of which is the impact of the development of information and technological progress that is increasingly difficult to stem. Therefore, teacher empowerment is not enough to be done through education and training (training) teaching skills, more than that teacher empowerment should also be done through enlighten the spiritual and spiritual dimensions so as to be able to exude noble character while being able to internalize values and also the growth of religious awareness in students themselves by placing religion and all its teachings as a stronghold for the entry of various negative influences.